Estimation Level of IL-12 in Blood of Patients with Tuberculosis - Eklass N. Ali (Journal of Global Pharma Technology, 2018)
Background: Tuberculosis (TB) is caused by mycobacterium tuberculosis; which is considered as one of the most common infectious diseases and major cause of morbidity and mortality worldwide. Methodology: The study included 45 patients with TB (38 males and 7 females) with age range between (10-69) years, and 16 apparently healthy subjects (as control) (14males and 2 females) who have been collected from the Specialized Center for Chest and Respiratory Disease in Baghdad. Specimens from TB patients were divided into three subgroups: 21 specimens from new diagnosis, 13 specimens from old patients (under treatment) and 11 specimens from Multi Drug Resistance (MDR). This study included bacteriological tests such as smear microscopy by ziehl-Neelsen stain for sputum samples and immunological diagnosis by estimation the concentration of cytokine (IL-12) and control by Enzyme Linked Immune sorbent Assay ELISA technique has been applied for patients and healthy groups (control), all TB patients sample were positive by smear microscopy. Results: This study showed a significant increase in the serum level rate of IL-12 in the patients (82.1)pg/ml comparing with the control group (48.9) pg/ml whereas The serum level of IL-12 in new cases & MDR TB was elevated than in old cases (p<0.05) and the concentration of IL-12 was significantly increased among young age (10-19) compared to other age group and was non-significant increased among females. The prevalence of fever, positive chest-X-ray finding, weight loss were more among the newly diagnosed patients (p<0.05) while the prevalence of positive DM patients was more among old cases (p<0.05). This study verified the correlation between the serum levels of IL-12 with different clinical forms of tuberculosis. It was reduced in patients with positive DM (71.8) pg/ml in comparison with patients with Negative DM (95.89) pg / ml with statistically significant differences between two groups (p<0.05). Conclusion: the high serum level of IL-12 in TB patients indicate an important role of these cytokine in the pathogenesis of tuberculosis, so they could be considered as good biomarker for diagnosis and considered as a target for future therapy. Keywords: TB, MDR, IL-12, chest-X-ray.